Learning the rules of the game: The role of generic "you" and "we" in shaping children's interpretations of norms. Issue 1 (17th August 2022) - Orvell, Ariana; Elli, Giulia; Umscheid, Valerie; Simmons, Ella; Kross, Ethan; Gelman, Susan A.
Abstract: A critical skill of childhood is learning social norms. We examine whether the generic pronouns "you" and "we, " which frame information as applying to people in general rather than to a specific individual, facilitate this process. In one pre‐registered experiment conducted online between 2020 and 2021, children 4‐ to 9‐year‐old primarily living in the midwestern U.S. ( N  = 146, 75 girls, 71 boys, M age  = 7.14, SD  = 1.69, 82% White) interpreted actions described with generic pronouns (vs. "I") as normatively correct and selected the speaker who used generic pronouns as the rule‐follower, particularly when generic pronouns were presented first. There were no significant effects of age. These results illustrate how generic pronouns influence how children discern unfamiliar norms and form interpersonal judgments.